1995
DOI: 10.1590/s0074-02761995000600003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Didelphis albiventris and Triatoma infestans in relation to Trypanosoma cruzi transmission

Abstract: This paper attempts to prove if a high Trypanosoma cruzi prevalence of opossums might be reached with few potential infective contacts. One non-infected Didelphis albiventris to T. cruzi and 10 infected nymphs of Triatoma infestans were left together during 23 hr in a device that simulated a natural opossum burrow. Twenty-six replicates were performed using marsupials and triatomines only once. Potentially infective contacts occurred in all the trials. From the 26 opossums used in trials, 54% did not eat any b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…In a laboratory device that simulated a natural opossum burrow, in which different opossums were independently challenged for 23 hr with 10 infected T. infestans, 29% of the opossums became infected (40% among the opossums that ingested triatomines and 21% among the ones that did not ingest triatomines). Experimental opossum infections in the laboratory resulted in prevalences similar to those observed in the field, 14 suggesting that for adult D. albiventris, a few infective contacts with infected triatomines might be sufficient to produce infection. Males are found infected in nature less frequently than females, and very rarely become infected experimentally (Schweigmann N, unpublished data).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…In a laboratory device that simulated a natural opossum burrow, in which different opossums were independently challenged for 23 hr with 10 infected T. infestans, 29% of the opossums became infected (40% among the opossums that ingested triatomines and 21% among the ones that did not ingest triatomines). Experimental opossum infections in the laboratory resulted in prevalences similar to those observed in the field, 14 suggesting that for adult D. albiventris, a few infective contacts with infected triatomines might be sufficient to produce infection. Males are found infected in nature less frequently than females, and very rarely become infected experimentally (Schweigmann N, unpublished data).…”
Section: Introductionmentioning
confidence: 62%
“…The experiment consisted of 13 replicates, each with one female opossum and a random mixture of 10 third and fourth instar triatomines. 14 The device used simulated a natural opossum burrow: a hardboard cage (50 ϫ 50 ϫ 45 cm) with one of the walls containing a removable wooden panel that acted as a shelter for triatomines, a fine wire net window for ventilation, and sand on the floor to absorb moisture. Opossums were starved for 1-2 days, and infected triatomines were fasted for 20-30 days before the trials.…”
Section: Sources Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a strong relation among pregnant females, peridomestic nests and triatomines can be established in this study. Previous studies in Yucatán had found opossum blood in the digestive tract of T. dimidiata (Quintal & Polanco 1977) and opossums are known to get infected by ingesting triatomines as well (Yaeger 1971, Schweigmann et al 1995; in Costa Rica, Zeledón (1970) associated the presence of T. dimidiata inside opossums nests with the high indices of infection found in the vector. Thus, the contact of pregnant females with infected triatomines inside the peridomestic nests would increased exposition to the infection and explains the higher infection rate of reproductive females found in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Several behavioral (synanthropism, nomadic habits, use of hollow trees and palms as refuges) and biological traits (two generations/year, life-long T. cruzi infection with long-lasting parasitemia) of this opossum make it a good candidate link between wild and peridomestic cycles of T. cruzi transmission, even in areas where stable, domiciliated vector colonies are uncommon 13,14,34,36,39,40 . The relatively low specific infection rate we found (14%) rises to 33% when considering only the gallery forest where most opossums were captured (RF, 18 individuals).…”
Section: Discussionmentioning
confidence: 99%